Transformative Epistemology in Advancing Contemporary Islamic Education: Knowledge Reconstruction Integrative-Nuraniyah Perspective - Rinda Fauzian; Juju Saepudin; Saehudin Saehudin (STAI Al-Mas'udiyah, 2025)
The aim of this study is to explore and analyze the concept of transformative epistemology in the development of contemporary Islamic education, with a focus on knowledge reconstruction from an integrative-nuraniyah perspective. This research adopts a qualitative approach with critical analysis of literature and concepts related to Islamic epistemology and contemporary Islamic education. Data were collected through library research, encompassing books, journal articles, and previous studies relevant to transformative epistemology, knowledge reconstruction in Islamic education, and the integration of spiritual aspects in teaching. The analysis process was carried out using a descriptive-analytical approach to identify gaps in the development of Islamic education and how transformative epistemology can provide solutions. The results show that transformative epistemology, which combines rational and spiritual dimensions, can serve as a strong foundation for reconstructing knowledge in contemporary Islamic education. This approach enables the development of a more comprehensive curriculum that emphasizes not only cognitive aspects but also spiritual and moral dimensions aligned with the demands of the times. The implementation of this epistemology has the potential to produce a generation that is not only intellectually capable but also ethically and spiritually aware. The implication of this research is the importance of integrating transformative epistemology into the Islamic education curriculum, with attention to spirituality and ethics, in order to address the increasingly complex challenges of contemporary education.